Advantages of Using an Air Purifier for the Control of Atopic Dermatitis - Nagara, Adianto Jaya; Rina Gustia (HM Publisher, 2024)
Numerous studies have been carried out to ascertain the detrimental impact of air pollution on allergy conditions such as asthma, allergic rhinitis, and atopic dermatitis. Substandard indoor air quality exacerbates atopic dermatitis, which can be attributed to several reasons. Proper air circulation is crucial in households, especially in areas with high foot activity, since it can lead to elevated amounts of air contaminants entering the space. Indoor air pollutants, such as house dust mites, volatile chemical compounds, particle matter, and indoor mold, can aggravate atopic dermatitis. An air purifier effectively enhances the quality of indoor air. This gadget offers significant advantages for those with atopic dermatitis by effectively mitigating the frequency and intensity of disease relapses.